1998
DOI: 10.1002/bbpc.19981020206
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion on simple heterogenous surfaces

Abstract: In this work we use the well‐known bivariate trap model with random topography in order to study the effects of surface heterogeneities on surface diffusion. Utilizing Monte Carlo simulations we characterize how the tracer, jump and chemical diffusion coefficients depend on temperature and concentration of deep traps, θ. In order to calculate the chemical diffusion coefficient we apply the fluctuation and the Kubo‐Green methods. Both methods are in good agreement at large values of θ only. The discrepancies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Here, we have used both methodologies with the same accuracy. The thermodynamic factor entering the expression for the chemical diffusion coefficient [31][32][33][34] can be directly obtained from Fig. 3.…”
Section: θ(µ) =mentioning
confidence: 99%
“…Here, we have used both methodologies with the same accuracy. The thermodynamic factor entering the expression for the chemical diffusion coefficient [31][32][33][34] can be directly obtained from Fig. 3.…”
Section: θ(µ) =mentioning
confidence: 99%
“…One of the aspects requiring a better understanding is the way in which the energetic topography affects different adsorption processes. In fact, even though it has been shown that many molecular surface processes are indeed dependent on the way adsorptive energy is spatially distributed on the surface (topography) [20][21][22], a systematic study showing how the main characteristics determining the topography act on the percolation of adsorbed particles at equilibrium is far to be exhausted. The present work intends to be a new step in this direction.…”
Section: Introductionmentioning
confidence: 99%